Strategy execution and firms' performance: A qualitative investigation of Nigeria's manufacturing sector - Nkemdilim Iheanachor (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
This study aimed to ascertain the role of strategy execution on the performance of the manufacturing sector in Nigeria using one of Africa's largest manufacturing conglomerates as a case study. A qualitative research design was deployed to actualize the above purpose by using a sample of eleven interviewees comprising five directors and other six members of the top management team from different departments of the firm whose headquarter is located in Lagos. The study revealed that all issues pertaining to strategy execution in the case study firm are the sole responsibility of the top management team led by its founder and president, which is consistent with theory. However, the interpretation of the interviewees' reactions implies that the firm did not have an explicitly understood strategy because it stems beyond merely setting objectives or targets. As such, the firm's overall performance cannot be linked to successful strategy execution. Nevertheless, there is a need for the case study firm and the industry to put measures in place to ensure improved communication at all levels, improved strategy development, reward system, performance monitoring, accountability and goal re-assessment where necessary. The measures mentioned above will aid the process of bridging the gaps in the overall performance of the case study firm in particular and the manufacturing industry in general.
Keywords: M12; M14; M16; 330; Strategy execution; firm performance; top management team; manufacturing conglomerate; qualitative research and Nigeria